2013
DOI: 10.1016/j.brainres.2012.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Calpain cleaves methionine aminopeptidase-2 in a rat model of ischemia/reperfusion

Abstract: Ischemic stroke results in multiple injurious signals within a cell including dysregulation of calcium homeostasis. Consequently, there is an increase in the enzymatic activity of the calpains, calcium dependent proteases that are thought to contribute to neuronal injury. In addition, cellular stress due to ischemia/reperfusion also triggers a decrease in protein translation through activation of the unfolded protein response (UPR). In the present study we found that methionine aminopeptidase 2 (MetAP2), a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Recently, Clinkinbeard et. al., reported that human p67 also has auto-proteolysis activity that generates p52 segment of this protein and this activity is further augmented by a metalloproteinase, calpain (12). We therefore believe that the faster migrating proteins like p52 and p26 are the cleavage products of full-length p67, which may have originated from ~2.2 kb transcript whereas, ~60 kDa protein may coming from the translation of ~1.4 kb transcript from mice.…”
Section: Fig4 Immunoblot Analysis Of Mouse P67 In Multiple Tissues Fmentioning
confidence: 95%
“…Recently, Clinkinbeard et. al., reported that human p67 also has auto-proteolysis activity that generates p52 segment of this protein and this activity is further augmented by a metalloproteinase, calpain (12). We therefore believe that the faster migrating proteins like p52 and p26 are the cleavage products of full-length p67, which may have originated from ~2.2 kb transcript whereas, ~60 kDa protein may coming from the translation of ~1.4 kb transcript from mice.…”
Section: Fig4 Immunoblot Analysis Of Mouse P67 In Multiple Tissues Fmentioning
confidence: 95%
“…By using pharmacological inhibitors or mice deficient in calpain-1 or calpain-2 or mice over-expressing calpastatin, the endogenous inhibitor, many studies demonstrated that inactivation of calpain inhibited the atherosclerosis, suggesting that calpains gets involved in the pathogenesis of atherosclerosis (Clinkinbeard et al 2013;Hua and Nair 2015;Miyazaki et al 2013;Ruetten and Thiemermann 1997;Takeshita et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Among the superfamily, Calpain-1 and calpain-2 are categorized as "conventional calpain" (Daugherty et al 2000). By using pharmacological inhibitors or mice deficient in calpain-1 or calpain-2 or mice over-expressing calpastatin, the endogenous inhibitor, many studies demonstrated that inactivation of calpain inhibited atherosclerosis, suggesting the involvement of calpains in the development of atherosclerosis (Clinkinbeard et al 2013;Hua and Nair 2015;Miyazaki et al 2013;Ruetten and Thiemermann 1997;Takeshita et al 2013). We previously reported that calpain-1 gets involved in the atherogenesis by up-regulating the scavenger receptor CD36 expression (Yang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Calpains recognize various intracellular substrate molecules, thereby controlling cellular activities. Numerous in vivo and in vitro experiments employing genetic and pharmacological approaches have focused on the roles of calpains in cardiovascular diseases [ 19 23 ]. Calpain-1 was increased in calcified aortic wall of rats with ageing at levels of transcripts, protein, and activity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%